The Influence of Teacher Competence on Student Learning Outcomes in Product, Creativity, and Entrepreneurship Subjects with Learning Discipline Mediation - Novi Satria Pradja (Jurnal Penelitian Pendidikan IPA, 2025)
The problem in this study is the learning discipline and student learning outcomes of class XI students at the SMK Muhammadiyah in Kuningan which are not optimal. This is shown from the scores of students who have scores below the KKM, this shows that student learning outcomes are still low. The purpose of this research is to find out the description of teacher competence, learning outcomes and learning discipline of Muhammadiyah Vocational High School students in Kuningan. The method used in this research is survey method and descriptive research and mediation method. The sample used was 191 class XI students at SMK Muhammadiyah in Kuningan. The results showed that the effect of teacher competence on learning outcomes was known. The results of testing and analysis showed that teacher competence was significant for learning outcomes with a significance value of 0.010 and a regression coefficient (c) = 0.185; the effect of teacher competence on learning discipline it is known that the results of testing and analysis show that teacher competency is significant for learning discipline with a significance value of 0.030 and the regression coefficient (a) = 0.157; Learning Discipline mediates the influence of Teacher Competence on Learning Outcomes, it is known that the results of testing and analysis show that teacher competence is significant for learning outcomes, after being mediated by learning discipline with a significance value of 0.031 and a regression coefficient (b) = 0.191; The effect of Teacher Competence on Learning Outcomes is reduced (c'= 0.155 <c = 0.185) and significant 0.031 after being mediated by learning discipline. It can be concluded that this model is included inpartial mediation or partial mediation occurs, meaning that learning discipline partially mediates the influence of teacher competence on learning outcomes.